Strategi Komunikasi Organisasi dalam Menanggulangi Radikalisme di Perguruan Tinggi Islam Jember - Wahidi, Achmad (Maddah: Journal of Advanced Da'wah Management Research, 2024)
The issue of religious radicalism is more frequently heard than the issue of moderate Islam, emancipatory Islam, and even more so than the discourse on liberal Islam itself. In fact, the issue of radicalism is more prominent compared to various other important issues. Following the Bali bombings on October 12, 2002, the JW Marriott Hotel bombing in Jakarta on August 5, 2003, and July 17, 2009, the Kuningan bombing in Jakarta on September 9, 2004, the Sarinah bombing on January 14, 2016, the Kampung Melayu bombing on May 24, 2017, and the events in Surabaya on Sunday, May 13, 2018, from 06:00 to 08:00 WIB, these incidents have destroyed buildings and claimed hundreds of lives. Therefore, the researcher aims to understand what Islamic higher education institutions are doing to counter these illicit ideologies. This study aims to understand the Organizational Communication Strategy in countering radicalism in Islamic higher education institutions. This research uses a qualitative method with field research and descriptive data analysis. The results of this study show that the Islamic University of Jember synergizes between the government and campus elements and also utilizes mass media to disseminate moderate Islam to students and the general public to counter radicalism.